Sistem-Sistem Pemerintahan Sedunia : Ragam Bentuk dan Sistem Pemerintahan Negara - Negara di Dunia - Radis Bastian (Ircisod, 2015)
Sistem-Sistem Pemerintahan Sedunia : Ragam Bentuk dan Sistem Pemerintahan Negara - Negara di Dunia